Are electoral autocracies better for the poor? Evidence from social assistance programs. (August 2020) - Fails, Matthew D.
Autocratic elections occur on uneven playing fields, yet their regular contestation compels ruling parties to pay attention to citizens' demands. This claim is at the heart of research linking multiparty elections in autocracies to improvements in human development. Recent work, however, casts doubt on the theoretical and empirical basis of such claims. This paper addresses this debate by focusing specifically on the adoption of social assistance programs, an often theorized but seldom examined link in the chain connecting electoral autocracy with improvements in human development. I demonstrate that electoral autocracies are more likely to adopt these programs than closed autocracies and that the impact largely works through within-country changes in the presence of electoral authoritarianism. The results are consistent with the argument that such regimes are more responsive to citizens' demands. However, they also remind researchers that the goal of such regimes is to win elections; there is little preventing them from crafting targeted social policies that secure the loyalty of the voting public but without the attendant improvements in broad measures of human development. I conclude with suggestions for how future research can better understand how authoritarian governance shapes development outcomes.